The Macroeconomic Effects of Public Investment : Evidence from Advanced Economies - Abiad, Abdul (IMF Working Papers; Working Paper ;, 2015)
This paper provides new evidence of the macroeconomic effects of public investment in advanced economies. Using public investment forecast errors to identify the causal effect of government investment in a sample of 17 OECD economies since 1985 and model simulations, the paper finds that increased public investment raises output, both in the short term and in the long term, crowds in private investment, and reduces unemployment. Several factors shape the macroeconomic effects of public investment. When there is economic slack and monetary accommodation, demand effects are stronger, and the public-debt-to-GDP ratio may actually decline. Public investment is also more effective in boosting output in countries with higher public investment efficiency and when it is financed by issuing debt.